Cyclophilin E (CypE) Functions as a Positive Regulator in Osteoblast Differentiation by Regulating the Transcriptional Activity of Runx2 - Meiyu Piao; Sung Ho Lee; Yuankuan Li; Joong-Kook Choi; Chang-Yeol Yeo; Kwang Youl Lee (Cells, 2023)
Cyclophilin E (CypE) belongs to the cyclophilin family and exhibits peptidyl-prolyl cis-trans isomerase (PPIase) activity. It participates in various biological processes through the regulation of peptidyl-prolyl isomerization. However, the specific role of CypE in osteoblast differentiation has not yet been elucidated. In this study, we first discovered the positive impact of CypE on osteoblast differentiation through gain or loss of function experiments. Mechanistically, CypE enhances the transcriptional activity of Runx2 through its PPIase activity. Furthermore, we identified the involvement of the Akt signaling pathway in CypE’s function in osteoblast differentiation. Taken together, our findings indicate that CypE plays an important role in osteoblast differentiation as a positive regulator by increasing the transcriptional activity of Runx2.